Intra‐household double burden of overweight/obesity and anaemia: Evidence from 49 low‐and middle‐income countries - Ana Irache; Paramjit Gill; Rishi Caleyachetty (Wiley, 2022)
Abstract Globally, overweight/obesity is rising rapidly while anaemia persists. Nevertheless, evidence on their coexistence at the household level remains limited. Using data from the Demographic and Health Surveys, we quantified the magnitude, distribution and inequalities (i.e., estimates by wealth, education level and residence) in the intra‐household double burden (DBM) of overweight/obesity and anaemia among mothers and their children living in 49 low‐ and middle‐income countries (LMICs). The pooled prevalence of total intra‐household DBM was 17.2% (95% confidence interval [CI]: 15.6, 18.8); 16.2% (95% CI: 14.6, 17.9) for mothers with overweight/obesity and children with anaemia; and 2.8% (95% CI: 2.5, 3.1) for mothers with anaemia and children with overweight/obesity. South Africa had the highest prevalence of total DBM at the household level, affecting almost one in three households. Households with mothers with overweight/obesity and children with anaemia followed an inverse social gradient, with higher estimates found in the richest quintile, highest maternal education level and in urban areas; although with some variation across regions. The opposite was observed for mothers with anaemia and children with overweight/obesity. The largest inequality gaps were found for mothers with overweight/obesity and children with anaemia in Togo by household wealth (29.3%‐points; p < 0.001), in Ghana by maternal education level (28.0%‐points; p = 0.001) and in Niger by area of residence (25.2%‐points; p < 0.001). Although double‐duty actions might help accelerate action towards reducing malnutrition in all its forms, a comprehensive assessment of the causes of anaemia is first warranted to design effective country‐specific programmes.